El ecofeminismo: la inclusión de la ética del cuidado a la reflexión sobre la crisis ambiental - Castro-Bernardini, Ximena (2024)
In this research, a review is made of the contribution of constructivist ecofeminism to the analysis of the environmental crisis. This ecofeminism proposes including gender categories and approaches of theoretical feminism in the analysis of the current environmental situation. Figures from the last year on the sexual division of labor - domestic and paid - in Latin America have been reviewed with the aim of identifying and highlighting the inequality of the sexual division of labor while recognizing that care work is still awarded in its majority to women. This article will show that the universalization of care experiences that are taken up from the ecofeminism of Alicia Puleo and in the Ethics of Care can be of vital importance as a measure of transformation of the relationship between human beings and nature.